Pengaruh penyuluhan gizi menggunakan media buku saku terhadap sarapan di SMPIT Al-Fityan School Aceh - Rukhma Alivia; Eva Fitriyaningsih (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Many adolescents skip breakfast, resulting in decreased concentration, easy fatigue, and long-term health problems. One of the efforts that can be done is to provide nutrition counseling that aims to improve the knowledge and ettitudes of adolescents about the importance of breakfast.Objectives: To escribe the effect of counseling with pocketbooks in improving the knowledge and attitudes of female students about the importance of breakfast at SMPIT Al-Fityan School Aceh.                                                                                                                Methods: This study is quantitative in nature with a Quasi-Experimental (One Group Pretest-Posttest Design) approach. The subjects were selected using total sampling, totaling 21 female students. The research was conducted at SMPIT Al-Fityan School, Aceh. Data analysis used the T-Test.                                                                                             Results: After conducting statistical tests using Dependent T-Test, the average knowledge and attitudes of the students before receiving counseling with pocketbook media were 11,76 and 45,04, respectively. After the counseling, the average values increased to 15,38 for knowledge and 53,71 for attitudes. The T-Test resulted in significant values for knowledge (0,001) and attitudes (0,000).Conclusion: There is an influence of nutritional counseling using pocketbook media on improving knowledge and attitudes regarding the importance of breakfast.